2005
DOI: 10.1177/0091270005280787
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Metabolic Activity of CYP2C19 and CYP3A in Relation to CYP2C19 Genetic Polymorphism in Chronic Liver Disease

Abstract: To study whether chronic liver disease (CLD) and genetic polymorphism affect the hepatic activity of cytochrome P450 (CYP) isoforms, we compared in vivo CYP2C19 and CYP3A activities using 3-hour omeprazole hydroxylation index (plasma concentration ratio of omeprazole to its 5-hydroxylated metabolite; a higher index indicates lower CYP2C19 activity) and partial formation clearance of cortisol to 6beta-hydroxycortisol (CL(cortisol-->6beta-HC)) in 31 CLD patients (9 with chronic hepatitis; 22 with cirrhosis compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 34 publications
2
22
1
Order By: Relevance
“…Ohnishi et al. 6 classified 31 patients with chronic liver diseases including chronic hepatitis and liver cirrhosis, and 30 healthy volunteers in terms of their CYP2C19 genotype and detected CYP2C19 activity with the omeprazole probe. They found that CYP2C19 activity in patients with chronic liver disease was significantly lower than that in healthy controls regardless of PM or EM.…”
Section: Discussionmentioning
confidence: 99%
“…Ohnishi et al. 6 classified 31 patients with chronic liver diseases including chronic hepatitis and liver cirrhosis, and 30 healthy volunteers in terms of their CYP2C19 genotype and detected CYP2C19 activity with the omeprazole probe. They found that CYP2C19 activity in patients with chronic liver disease was significantly lower than that in healthy controls regardless of PM or EM.…”
Section: Discussionmentioning
confidence: 99%
“…CYP2C19 has been identified as one of the more sensitive P450s to the presence of liver diseases such as hepatocellular carcinoma, hepatitis C, and chronic hepatitis and cirrhosis (Ohnishi et al, 2005;Frye et al, 2006). In addition, it has also been shown to be affected earlier than the other important drug-metabolizing P450s (Villeneuve and Pichette, 2004).…”
Section: Fisher Et Almentioning
confidence: 99%
“…Clinical studies confirm that the urinary metabolic ratio of caffeine, mephenytoin, debrisoquine, and chlorzoxazone, which are in vivo probes of CYP1A2, 2C9, 2D6, and 2E1, respectively, is reduced (Ohnishi et al, 2005;Frye et al, 2006). However, there is a paucity of data on the effect of cirrhosis on expression and activity of hepatic drug transporters (Ogasawara et al, 2010;More et al, 2013).…”
Section: Introductionmentioning
confidence: 99%